MicroRNAs that interfere with RNAi - Massirer, Katlin B. (Landes Bioscience, 2013)
A recent study by Massirer et al. in the nematode C. elegans has shown that a family of microRNAs (miRNAs), miR-35-41, regulates the efficiency of RNA interference (RNAi), revealing a new connection between these small RNA pathways. In this commentary, we discuss the potential mechanisms for cross regulation in the miRNA and RNAi pathways and the implications for gene expression. While miRNAs are genetically encoded, the small interfering RNAs (siRNAs) that function in RNAi can originate from processing of exogenous dsRNA (exo-RNAi) or from the production of siRNAs from endogenous transcripts (endo-RNAi). These small RNA pathways involve Dicer and Argonaute proteins and typically use antisense base pairing to target mRNAs for downregulated expression. The discovery that loss of miR-35–41 results in enhanced exo-RNAi sensitivity and reduced endo-RNAi effectiveness suggests that these miRNAs normally help balance the RNAi pathways. The effect of mir-35–41 on RNAi is largely through lin-35, the C. elegans homolog of the tumor suppressor Retinoblastoma (Rb) gene. lin-35/Rb previously has been shown to regulate RNAi sensitivity through unclear mechanisms and the new finding that accumulation of LIN-35/Rb protein is dependent on miR-35–41 adds another layer of complexity to this process. The utilization of miRNAs to control the responsiveness of RNAi exemplifies the cross-regulation embedded in small RNA-directed pathways.